Analysis Of Factors Associated With The Incidence Of Pulmonary Tuberculosis (TB) In The Working Area Of The Pekauman Community Health Centre In Banjarmasin City - Nur Azizah; Eko Suhartono; Lenie Marlinae; Rosihan Adhani; Isna Syauqiah (An-Nadaa : Jurnal Kesehatan Masyarakat (e-Journal), 2025)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis which is transmitted through airborne transmission (droplets) when the patient coughs or sneezes. Tuberculosis (TB) will affect several aspects of life, including the economic aspect where TB patients will lose average working time and affect income, social aspects in the form of community stigma regarding TB disease, and psychological aspects in the form of anxiety, decreased support and low self-confidence. Puskesmas Pekauman ranked first for the highest TB incidence rate in Banjarmasin City with 73 cases. Based on the data above, it can be concluded that pulmonary TB cases tend to increase and most of the TB incidence is experienced by the productive age group (15-54 years). This study aims to analyze the risk factors associated with the incidence of pulmonary TB in the Pekauman Puskesmas area of Banjarmasin City. This study used a retrospective method using a case control approach, with the population in this study were people aged 15-54 years who suffered from pulmonary TB disease. he sample calculation using the 2-group proportion difference test in this study was 60 samples consisting of 30 respondents as a case group and 30 other respondents as a control group. observation and measurement sheets using a roller meter, lux meter, and thermohygrometer. Dependent variable: pulmonary TB disease. Independent variables: smoking habit, ventilation area, lighting, humidity, temperature, and house occupancy density. The results showed no significant relationship between smoking habits (p=0.073), ventilation area (p=constant), temperature (p=1.000), humidity (p=1.000), and house occupancy density (p=0.091) with the incidence of pulmonary TB, and there was a significant relationship between lighting and the incidence of pulmonary TB (p=0.027),. The smoking habit variable was the most dominant factor associated with the incidence of pulmonary TB, with an Exp(B) value = 5.654.